PATIENT SELF DELAY AMONG WOMEN WITH BREAST CANCER - Khan, Ayesha; Khan, Khalid; Raza, Ali; Qureshi, Zaheer ud Din; Sultan, Babar; Khan, Fahad Ali (Journal of Ayub Medical College Abbottabad, 2018)
Background: Delay in the diagnosis of carcinoma breast has important prognostic, clinical and medico-legal implications. This study assesses the frequency and causes of patient delay in women with breast cancer presenting to a breast clinic run by a specialist surgical unit in a tertiary care hospital. Methods: For this study all women, aged between 16-90 years, who presented with primary breast carcinoma of any histological type, diagnosed between June 2016 to September 2017 were eligible. Structured interviews were administered during the first visit with a confirmed diagnosis or the first hospitalization due to carcinoma breast, and the frequencies of the factors for delay analysed. Results: 84% of the patients presenting with primary carcinoma breast present with a significant patient delay, of which older patients who are illiterate, poor, coming from rural areas and unaware of carcinoma breast as a disease, among other factors, have a higher tendency to delay consultation. Conclusion: Healthcare advice-seeking behaviour in women suffering from breast cancer in Pakistan is alarming with a vast majority of patients presenting late leading to delayed treatment and probable worse outcomes and survival. Keywords: carcinoma breast; self-delay; late diagnosis; patient delay; breast cancer